The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2020
DOI: 10.1097/bpo.0000000000001615
|View full text |Cite
|
Sign up to set email alerts
|

Inter-rater and Intrarater Reliabilities of the Identification of a “Gothic Arch” in the Acetabulum of Children With Cerebral Palsy

Abstract: Background: Progressive hip displacement in children with cerebral palsy (CP) is monitored by measuring migration percentage (MP) on anteroposterior (AP) pelvis radiographs. Accurate measurement of MP requires the lateral margin of the ossified acetabulum to be identified for the placement of Perkin’s line. It has been suggested that when there is an erosion of the acetabular rim, described as a gothic arch, the midpoint of the arch be used for the placement of Perkin’s line. However, this require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 25 publications
1
1
0
Order By: Relevance
“…For all three of these scenarios, we were close to achieving consensus but failed. These results support the recent findings of Miller et al, 22 who reported that there was poor inter and moderate intra-rater reliability in identifying a gothic arch on an AP pelvis radiograph. This lack of agreement here may make the identification of a gothic arch, or more importantly, identification of a hip that is at risk delayed and could negatively impact the time to referral to a pediatric orthopaedic surgeon.…”
Section: Discussionsupporting
confidence: 91%
“…For all three of these scenarios, we were close to achieving consensus but failed. These results support the recent findings of Miller et al, 22 who reported that there was poor inter and moderate intra-rater reliability in identifying a gothic arch on an AP pelvis radiograph. This lack of agreement here may make the identification of a gothic arch, or more importantly, identification of a hip that is at risk delayed and could negatively impact the time to referral to a pediatric orthopaedic surgeon.…”
Section: Discussionsupporting
confidence: 91%
“…MP, as first described by Reimers, 17 is currently the gold standard for radiological assessment of hip displacement in CP and the basis for hip surveillance. Measuring MP should be done with caution, as there are many factors that can decrease the accuracy of the measures such as patient positioning, 25 defining the lateral border of the acetabulum, 26 and clinician’s experience. When MP measurements were done by five different clinicians with different expertise, Demir et al 27 found excellent inter- and intrarater reliability.…”
Section: Discussionmentioning
confidence: 99%